"My people shall not be poor”: mosque-based microfinance model and poverty alleviation among Nigerian muslims (2008)
Even though various Governmental and Non-Governmental Organisations have risen up to the challenge of alleviating poverty and reducing income inequality in Nigeria through the medium of microcredit and microfinance, the efforts appeared to be plagued by inept performance, low outreach and religious beliefs of Muslims. Concerned about these challenges, this paper suggests an alternative way of delivering credit and credit-plus services to Muslims in Nigeria through the utilisation of the mosque and Islamic financial instruments. It argues that using the platform of the mosque for microfinance will increase outreach, improve efficiency and reduce running costs. In addition, Islamic financial instruments could boost the funds which will be made available to the poor.